Utilization of Tamarind Seeds Extract as a Natural and Sustainable Fabric Dye - Istyami, Astri Nur; Arif, Muhammad; Azzindi, Muhammad Ilham; Pratiwi, Meiti; Adisasmito, Sanggono; Damayanti, Nuning Yanti; Bustomi, Agus Tendi Ahmad; Rizkiana, Jenny (Indonesian Journal of Chemical Research, 2024)
This research focuses on the use of tannin components in tamarind seed coats as a mordant and natural dye in cotton fabrics. Tannins were extracted from the tamarind seed coat by boiling method and then the tannin content was determined. The tannin extract was then used as a natural mordant with the addition of metallic copper sulfate (CuSO4) mordant. Tannin extract is also used as a dye on fabrics with the addition of sodium sulfate (NaSO4). The color strength of the tannins in the fabric was analyzed using a spectrophotometer from the rinse water. The results showed that the cloth that had been given the mordant had a stronger color strength than the cloth without the mordant. The use of mordant was varied at concentrations of 5, 10, 15, 20, and 25%-owf. The results of the analysis showed the most optimum tannin concentration at 15%-owf. The concentration of tannin used in the coloring process was also varied at concentrations of 5, 10, 15, 20, and 25%-owf. The results of the analysis show that the concentration of tannin used in the dye does not affect the strength of the color, but only affects the brightness of this color.